With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Colonialism/postcolonialism - Loomba, Ania (Routledge, 1998)
Colonialism/Postcolonialism est un guide complet mais accessible sur les dimensions historiques, théoriques et politiques des études coloniales et postcoloniales. Ania Loomba examines the key features of the ideologies and history of colonialism, and the relationship of colonial discourse to literature. She goes on to consider the challenges to colonialism, surveying anti-colonial discourses, and recent developments in postcolonial theories and histories. Looking at how sexuality is figured in the texts of colonialism, Colonialism/Postcolonialism shows how contemporary feminist ideas and concepts intersect with those of postcolonialist thought
https://ebookcentral.proquest.com/lib/uqam/detail.action?docID=168653
Keywords: approches et analyses; arts; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; ressource en ligne; thématiques; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Postcolonial subjects: Francophone women writers - Green, Mary (University of Minnesota Press, 1996)
Sujets postcoloniaux » est un projet collectif centré sur les questions de langue, d'identité et de voix alors qu'ils abordent les questions de genre, de race, d'ethnicité, de culture et de nation. Les essais critiques présentés ici portent sur les contributions littéraires de femmes contemporaines écrivant en français dont les liens culturels, les identités ethniques et les racines historiques se situent au-delà de l'Hexagone, au-delà de la carte à six faces de la France.
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; francophonie; féminisme décolonial; littérature; premier cycle; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

Woman, native, other: Writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press., 1989)
"" ... Methodologically innovative ... precise and perceptive and conscious ... ""–Text and Performance Quarterly""Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color.""–Chandra Talpade Mohanty""The idea of Trinh T. Minh-ha is as powerful as her films ... formidable ... ""–Village Voice"" ... its very forms invite the reader to participate in the effort to understand how language
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; fem1000; fem3200; féminisme décolonial; littérature; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Le texte « La conciencia de la mestiza : Toward a New Consciousness » a été donné en lecture au cours POL4212.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Je suis une maudite sauvagesse = Eukuan nin matshimanitu innu-iskueu - Antane Kapesh, An (Leméac, 1976)
An Antane Kapesh signe un réquisitoire accablant contre les Blancs : « Quand le Blanc a voulu exploiter et détruire notre territoire, il n'a demandé de permission à personne, il n'a pas demandé aux Indiens s'ils étaient d'accord. »
Donné en lecture au cours POL5480, Chapitre 6 « La police et les tribunaux », p. 109-144 dans la dernière édition.
Keywords: amériques; approches et analyses; autochtones; cours; discipline; fem1000; fem3100; femmes* innues; féminisme décolonial; littérature; manifeste; militance; pol4105; pol5480; premier cycle; premières nations; québec; racisme; racisme systémique; régions géographiques; systèmes d'oppressions; thématiques; études littéraires